2022
DOI: 10.3390/genes13020321
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer with Mutation in BRCA1/2, MLH1, and APC Genes: Phenotype Correlation and Detection of a Novel Germline BRCA2 Mutation

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the seventh leading cause of cancer death worldwide; most of cases are sporadic, however about 5% to 10% report a hereditary predisposition. Several hereditary syndromes have been associated with familial pancreatic cancer (FPC) onset, including hereditary breast and ovarian cancer syndrome (HBOC), Lynch syndrome (LS), Familial atypical multiple mole melanoma (FAMMM), Familial adenomatous polyposis (FAP), Li–Fraumeni syndrome (LFS),Peutz–Jeghers syndrome (PJS), and He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Biallelic MUTYH mutations have been linked to MUTYH -associated polyposis syndrome (MAP). In the past few years, monoallelic MUTYH PVs have been found in patients with gastric, liver, endometrial, breast, ovarian and pancreatic cancer [ 36 , 37 ], and this has led to several studies investigating the impact of germline monoallelic MUTYH PVs in tumorigenesis. We found that 0.56% of families showed a monoallelic frameshift MUTYH PV, while a previous study reported MUTYH PVs in 2.37% of patients with a family history of prostate cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biallelic MUTYH mutations have been linked to MUTYH -associated polyposis syndrome (MAP). In the past few years, monoallelic MUTYH PVs have been found in patients with gastric, liver, endometrial, breast, ovarian and pancreatic cancer [ 36 , 37 ], and this has led to several studies investigating the impact of germline monoallelic MUTYH PVs in tumorigenesis. We found that 0.56% of families showed a monoallelic frameshift MUTYH PV, while a previous study reported MUTYH PVs in 2.37% of patients with a family history of prostate cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the direct implication of BRCA1/2 signaling in the pathophysiology of hereditary pancreatic adenocarcinoma (PDAC) [285], as well as the recently reported prognostic impact of HER2 expression or amplification in the survival of PDAC patients [286], we examined possible alterations in the expression profiles of BRCA1/2 and HER2 mRNAs In contrast, colon cancer mesenchymal cells do not express iNOS and instead overexpress eNOS that impairs the CSC phenotype and induces tumor cell proliferation [282]. The above findings indicate that the type and expression levels of each NOS isoform in CSCs might be specific to cancer type and tumor aggressive potential, as well as the impact of inflammation-induced iNOS and NO in tumorigenesis.…”
Section: Implication Of Inos Her2 and Brca1/2 In Csc Pathophysiologymentioning
confidence: 99%
“…Given the direct implication of BRCA1/2 signaling in the pathophysiology of hereditary pancreatic adenocarcinoma (PDAC) [285], as well as the recently reported prognostic impact of HER2 expression or amplification in the survival of PDAC patients [286], we examined possible alterations in the expression profiles of BRCA1/2 and HER2 mRNAs in our PDAC CSC models. Both MiaPaca2 and PANC1 cell lines are proficient in BRACA1/2 wildtype expression [287], while HER2 levels are more profound in MiaPaca2 than PANC1 [288].…”
Section: Implication Of Inos Her2 and Brca1/2 In Csc Pathophysiologymentioning
confidence: 99%
“…Most patients with pancreatic cancer are sporadic ( Vietri et al ., 2022 ) and the incidence of pancreatic cancer is estimated to increase further. The risk factors for pancreatic cancer include sex, smoking, alcohol consumption, diabetes and family history.…”
Section: Introductionmentioning
confidence: 99%